Reference evapotranspiration estimates in different cloudiness conditions - de Souza, Adilson Pacheco; de Carvalho, Daniel Fonseca; Duarte da Silva, Leonardo Batista; de Almeida, Frederico Terra; da Rocha, Hermes Soares (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the performance of reference evapotranspiration (ETo) estimation methods, in different cloudiness conditions, in Seropédica, RJ, Brazil. The ETo estimates were compared with daily measurements made on weighing lysimeter, between 6/1/2006 and 7/31/2007, by pooling the data or discretizing them according to the variance of daily clearness index (KT), in four classes: KT≤0.35, cloudy sky (Clo); 0.35
Keywords: Hargreaves-Samani; lysimeter; irrigation management; Penman-Monteith; atmospheric transmissivity